Numerical simulation of risk mitigation strategies for early-age thermal cracking and DEF in concrete. (7th March 2022) - Chiniforush, Alireza A.; Gharehchaei, Maryam; Akbar Nezhad, Ali; Castel, Arnaud; Moghaddam, Farzad; Keyte, Louise; Hocking, David; Foster, Stephen
Highlights: Numerical simulation of hydration heat transfer and thermal stress in early-age concrete. Investigating different mitigation strategies including: placement time during a day, lowering placement temperature, using heat blankets, changing type of aggregates, optimizing the mix, utilizing cooling pipes, and sequencing pours. Minimizing risk of thermal cracking and delayed ettringite formation in mass concrete pours. Abstract: Early-age thermal cracking and delayed ettringite formation (DEF) are short-term and long-term major issues to the durability of mass concrete and require a high level of consideration in the development of a suitable concrete mix design in placement and curing strategies, particularly in mixes of high cement content. Where DEF risk proves to be significant, contractors are required to adopt risk mitigation strategies including lowering concrete's temperature during placement by adding cool water or ice, for example, to the mix, embedding cooling pipes in the cast element and/or sequential placement of the concrete. These strategies can be implemented at different levels, as needed, to minimise the risk of cracking and DEF. Determining the most suitable and cost-efficient risk mitigation strategy, however, together with its implementation, is a complex task that requires consideration of each complex strategy under project-specific conditions. While a significant research effort has been invested to develop an improved understanding of the effectiveness of different early age thermal cracking and DEF risk mitigation strategies, the lack of reliable models capable of simulating and comparing the effectiveness of all scenarios remains elusive and considerably limits the ability of the practitioners in identifying the optimal approach. This paper presents a Multiphysics model developed to predict the effect of early-age thermal cracking and DEF risk mitigation scenarios. The model is validated using four real-life project Case Studies and is demonstrated to provide reliable results. In addition, the paper studies the comparative effectiveness of key risk mitigation strategies and the important parameters influencing their effectiveness.